'By Children, With Children, for Children': Exploring Children's Rights-Based Approaches Within an Educational Psychology Service Using Appreciative Inquiry - Joyce, Hannah (2024)
Children’s Rights-Based Approaches (CRBA) are holistically underpinned by the United Nations Convention on the Rights of the Child (UNCRC). Research highlights the benefits of adopting CRBA within education, to raise awareness of children’s rights, enhance participation, improve rights-consciousness, promote inclusion and ensure positive outcomes for children socially, emotionally and academically. Educational Psychologists (EPs) play a crucial role in upholding children’s rights, which are relevant to all facets of their practice. It is therefore essential for EPs to understand how to apply CRBA in practice, yet this has not been addressed in research. This study investigates how EPs define and implement CRBA, and identifies the factors that facilitate implementation, employing Appreciative Inquiry (AI) to support practice development. It also aims to evaluate AI as a tool for professional development within EP teams. Using a participatory action research design, the study engaged an EP team in Northern England in six workshops over seven months, as co-researchers in an AI that sought to develop their practice in using CRBA. The 5D cycle of AI, with an added evaluation phase was utilised. Data was gathered through participatory discussion based activities, and co-analysed using a participatory adaptation of reflexive thematic analysis. Data was recorded visually by participants, using a range of tools such as rich pictures and thematic maps. Findings indicate that EPs define CRBA contextually, and apply them broadly across all aspects of their work. Key factors that facilitate CRBA in practice include commitment, collaboration, confidence, care and creativity. The conceptual framework based on these factors, co-developed by participants is presented. This provides a reflective tool to guide practice and embed CRBA for the EP team in this study, which, if shared, has the potential to impact rights-respecting EP practice at a broader level.